Uma abordagem composicional da informação associada à geração de conhecimento - Bandeira, Francisco Dário de Andrade (2024)
The compositional approach of information (CAI) undertakes the philosophical effort to relate information and knowledge by explaining certain central features of information. It brings forward them in three levels of occurrence. These levels are explained progressively throughout the exposition. Firstly, the main theses of some studies on information are presented; they constitute the ground of the argument of this work. Secondly, other studies are discussed, which help to expose ontological and epistemic aspects of information and to exhibit its connections with related notions. At last, some possible applications of CAI are addressed, as well as some gaps and issues that may require further research.